2007
DOI: 10.1002/jssc.200700204
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of iridoids, phenolic acids, flavonoids, and saponins in Flos Lonicerae and Flos Lonicerae Japonicae by HPLC‐DAD‐ELSD coupled with principal component analysis

Abstract: A method, HPLC coupled with diode-array and evaporative light scattering detectors (HPLC-DAD-ELSD), was newly developed to evaluate the quality of Flos Lonicerae (FL) and Flos Lonicerae Japonicae (FLJ), through a simultaneous determination of multiple types of bioactive components. By employing DAD, the detection wavelengths were set at 240 nm for the determination of iridoids, 330 nm for phenolic acids, and 360 nm for flavonoids, respectively. While ELSD, connected in series after DAD, was applied to the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 6 publications
4
37
0
Order By: Relevance
“…As another type of pharmacologically important constituent, major iridoid glycosides have not been paid enough attention for the quality evaluation of LJF. A few investigations were reported involving in the quantitative analyses of iridoid glycosides, including sweroside, 7-epivogeloside, secoxyloganin, dimethyl-secologanoside, centauroside and loganin, along with phenolic acids and flavonoids, by HPLC-DAD-ELSD [22] and HPLC-DAD-MS [18,19,23]. However, from our study mentioned above, secologanic acid was the most abundant iridoid, and its content was far higher than those of sweroside and loganin, which were commonly used as the representatives of iridoid glycosides in LJF samples.…”
Section: Quantification Of Main Phenolic Acids Flavonoids and Iridoimentioning
confidence: 99%
“…As another type of pharmacologically important constituent, major iridoid glycosides have not been paid enough attention for the quality evaluation of LJF. A few investigations were reported involving in the quantitative analyses of iridoid glycosides, including sweroside, 7-epivogeloside, secoxyloganin, dimethyl-secologanoside, centauroside and loganin, along with phenolic acids and flavonoids, by HPLC-DAD-ELSD [22] and HPLC-DAD-MS [18,19,23]. However, from our study mentioned above, secologanic acid was the most abundant iridoid, and its content was far higher than those of sweroside and loganin, which were commonly used as the representatives of iridoid glycosides in LJF samples.…”
Section: Quantification Of Main Phenolic Acids Flavonoids and Iridoimentioning
confidence: 99%
“…According to their chromatographic retention behavior in HPLC reported before, the saponins with sugar moieties at the C-28 position eluted easier than that with sugar moieties at the C-3 position in RP-HPLC [23]. Thus C21 and C25 were tentatively identified as 1 ion at m/z 951.5117 in positive spectrum, and the molecular mass of C20 was 16 Da greater than that of C21 and C25, the elemental composition could be then undoubtedly assigned to C 47 H 76 O 18 (see [11,14].…”
Section: Saponinsmentioning
confidence: 89%
“…Chemical and pharmacological investigations revealed that four types of secondary metabolites, including phenolic acids, iridoids, saponins and flavonoids, are responsible for the overall therapeutic effects of Flos Lonicerae [10][11][12][13][14]. Flavonoids such as baicalein, baicalin, wogonin and wogonoside are the major active components in Radix Scutellariae [15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an on-line coupled HPLC-DAD-ELSD method has attracted ever-increasing attention and has been successfully applied to simultaneous quantification of multi-components in traditional Chinese herbal medicines and their preparations [14][15][16][17][18][19][20][21][22][23]. This method is potentially ideal for routine analysis and quality evaluation of YST since UV and ELSD signals contain complementary information for each other.…”
Section: Introductionmentioning
confidence: 99%